The Relationship Between The Accuracy of Filling Out The Early Warning Score System Form and Nurse Decision Making - Dewi Lindayani; Rika E Nurhidayah; R Kintoko Rochadi (Universitas Islam Negeri Sumatera Utara, Medan, 2024)
Early Warning Score System plays an important role in monitoring and tracking patient deterioration through vital signs and physical condition. Nursing decision making is a complex process that has the potential to influence the quality of care provided. Clinical decision making requires critical thinking skills for nurses. This study aims to analyze the relationship between the accuracy of filling out the Early Warning Score System form and nurses' decision making. The type of research used is quantitative research using a retrospective descriptive research design with a cross sectional descriptive research design. The sampling technique is purposive sampling. The respondents of this study were nurses in integrated inpatient rooms A and B at the Haji Adam Malik Central General Hospital, Medan. This research was carried out in the integrated inpatient ward at the Haji Adam Malik Central General Hospital, Medan. The sample consisted of 148 respondents in the inpatient ward. The instruments used were the standardized Early Warning Score System monitoring form at Haji Adam Malik Hospital and nurse decision making adopted from the Ekwantoro questionnaire. The data were analyzed using the Spearman rank test to obtain a correlation coefficient of +0.470 with a significant p-value = 0.000. The conclusion is that there is a relationship between the accuracy of filling in the Early Warning Score System formula and nurse decision making which is quite strong and in the same direction. It is recommended that nurses increase their in-depth understanding of filling out the Early Warning Score System form in order to make appropriate decisions in providing nursing care. Keywords: Accuracy of filling, Decision making, ERWSS